Transformational Leadership to Build Prophetic Culture (Multisite Study: SDI Makarimul Akhlaq Jombang and SDI Roushon Fikr Jombang) - Falah, Moh. Syamsul; Qomar, Mujamil; Munardji, Munardji (Technium Social Sciences Journal, 2021)
Transformational leadership is part of a very interesting and unique leadership model. This transformational leadership has implemented on four dimensions by Bass and Riggio: ideal influence of transformational leadership, inspirational motivation of transformational leadership, intellectual stimulation of transformational leadership, individual consideration of transformational leadership. This leader is as an agent of change who strengthen his knowledge, experience and ability. Especially if it is associated with the development of prophetic culture. At present, the study of prophetic culture can be categorized as a new trend. Although the nature of this prophetic culture has existed since the Prophets, it highlights more aspects of prophetic values. These prophetic cultural values carry Kuntowijoyo theory which is based on three pillars namely transcendence, humanization, and liberation. The research questions presenter on this dissertation are as follows: How is transformational leadership to build prophetic culture in SDI Makarimul Akhlaq Jombang and SDI Roushon Fikr Jombang? While purpose of the research is to explain the quistions that have been asked. This research is a qualitative research with a naturalistic phenomenological approach with multisite design. Techniques used for collecting the data are observation, interview, and documentation. Data analysis includes single site analysis and cross-site analysis. The techniques for analyzing the data are data reduction, data display and verification and conclusion. The results of this study are made of conclusion the dimension of transformational leadership in building by Bass and Riggio’s theory need to be added, namely partner stimulation because this partner stimulation can produce total leadership in building a professional culture. Likewise in Kuntowijoyo’s prophetic culture about theocentric-humanization that the concept of humanism-theocentric that Kuntowijoyo built from the findings of the study also provided additional as an existing development, namely theocentric-humanism-liberation because of the findings of researchers who showed infaq practices not only humanizing humans with based on faith alone, but indeed included in it is to free or free someone from distress.